2016
DOI: 10.1021/acs.jpcc.6b06589
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy Formation on α-MoO3 Slabs and Ribbons

Abstract: MoO3 is a versatile catalyst for oxidation reactions that consists of bilayers connected by van der Waals interaction. In principle a MoO3 nanocrystal can be exfoliated to create twodimensional ribbons. For this article, we study the difference between the chemistry of slabs having a variety of crystal faces and that of the edges of ribbons cut from a two-dimensional bilayer. As a descriptor of chemical reactivity we use the energy of oxygen-vacancy formation: the easier it is to form an oxygen vacancy, the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 120 publications
(198 reference statements)
8
50
0
Order By: Relevance
“…With Bader analysis, 86 the Bader charges on the oxygen atoms were found to be À0.68e, À0.99e and À1.10e, for the O1, O2 and O3 atoms respectively, with a Bader charge on the Mo of 2.77e. These results match within 8% the recent works of Agarwal et al 83 and Akande et al, 48 but have an up to 22% magnitude difference from older studies with no van der Waals treatment such as Coquet & Willock, 60 Sha et al, 53 and Lei & Chen, 52 indicating that van der Waals treatment has a noticeable effect on charge distributions in this material. Fig.…”
Section: Model Vericationsupporting
confidence: 90%
See 1 more Smart Citation
“…With Bader analysis, 86 the Bader charges on the oxygen atoms were found to be À0.68e, À0.99e and À1.10e, for the O1, O2 and O3 atoms respectively, with a Bader charge on the Mo of 2.77e. These results match within 8% the recent works of Agarwal et al 83 and Akande et al, 48 but have an up to 22% magnitude difference from older studies with no van der Waals treatment such as Coquet & Willock, 60 Sha et al, 53 and Lei & Chen, 52 indicating that van der Waals treatment has a noticeable effect on charge distributions in this material. Fig.…”
Section: Model Vericationsupporting
confidence: 90%
“…This work used the D3 treatment by Grimme, 62 while earlier studies used the D2, 47,80 the optB88-vdW 46,81,82 or in the case of early studies, 53,60,61 no treatment at all. The most common level of theory was GGA + U with a U parameter of 6.3 eV, however there were studies that used smaller U values, 83 no U parameter 53 or the HSE06 hybrid functional. 48 The band gap of the simulated structure of this work was found to be 1.5 eV, which is lower than the experimental values that range from 3 to 3.3 eV.…”
Section: Model Vericationmentioning
confidence: 99%
“…[ 33,34 ] It was reported that the formation of oxygen vacancies or Mo 5+ in the α‐MoO 3 host could cause the absorbance band in the longer wavelength region. [ 35–38 ] The electron paramagnetic resonance (EPR) spectra of M ceramic was measured to demonstrate the origin of the longer wavelength absorption. A distinct signal peak at g = 1.9948 of oxygen vacancies in M ceramic was found, [ 39–42 ] as displayed in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…For the DFT + U calculations of α-MoO 3 , a scattering range of U eff values from 1 to 8.6 eV have been used in the literature 21 . The value of U eff is usually empirically determined, and it is near impossible to find a universal U eff that is effective for all the different cases.…”
Section: Resultsmentioning
confidence: 99%
“…The recent work by Agarwal et al . explored the catalytic applications of the bulk MoO 3 and two-dimensional MoO 3 21 . Yang et al .…”
Section: Introductionmentioning
confidence: 99%